THU0051 PPAR-GAMMA Agonist Inhibits Migration and Invasion by Down Regulating TNF Alpha-Induced CYR61 Expression in Rheumatoid Arthritis-Fibroblast Like Synoviocyte. (9th June 2015) - Kwon, E.-J.; Cho, M.; Park, E.-J.; Kim, J.
Abstract : Background: Peroxisome proliferator-activated receptor gamma (PPARγ) agonist has anti-inflammatory properties, which has known to reduce inflammatory cytokine production in RA. Cysteine-rich angiogenic inducer 61 (Cyr61) is associated with diseases related to chronic inflammation. Cyr61, pro-inflammatory factor, has been shown to be increased in the synovial tissues of patients with RA. However the action mechanisms between Cyr61 and PPARγ are unknown. Objectives: The aim of this study was to investigate mechanism of PPARγ and its relation to Cyr61 in pathogenesis of RA. Methods: All synovial tissue were obtained from RA patients undergoing total joint replacement. RA-FLS were cultured with TNFα, and Cyr61 in the presence or absence of PPARγ agonist. Expression of the Cyr61 was estimated by RT-PCR and western blotting. The Cell migration and invasion was assessed by wound repair assays and transwell system. Results: Cyr61 protein was expressed on RA-FLS, and its expression was increased by TNFα. Moreover, Cyr61 directly promotes RA-FLS migration (p<0.01) and invasion (p<0.01) compared to the untreated RA-FLS. RSG significantly decreased TNFα-induced Cyr61 protein expression. Furthermore, not only did RSG inhibit TNFα induced RA-FLS migration distance (p<0.01) and invasion (p=0.018), but also decreased Cyr61 treated RA-FLS invasion (p<0.01). However, RSG did not affect Cyr61 gene expression in RA-FLS. Conclusions: Our result show that PPARγ agonist may have beneficial effects on migration and invasion of RA-FLS via down-regulation of Cyr61. Therefore, PPARγ agonist could be a potential treatment of RA. References: Jie LG, Huang RY, Sun WF, Wei S, Chu YL, Huang QC, et al. Role of cysteinerich angiogenic inducer 61 in fibroblastlike synovial cell proliferation and invasion in rheumatoid arthritis. Mol Med Rep 2015 Feb;11(2):917-923. Pang X, Wei Y, Zhang Y, Zhang M, Lu Y, Shen P. Peroxisome proliferator-activated receptor-gamma activation inhibits hepatocellular carcinoma cell invasion by upregulating plasminogen activator inhibitor-1 Cancer Sci 2013 Jun;104(6):672-680. Disclosure of Interest: None declared